Chironomid Research in Northern Patagonia - Donato, Mariano Humberto; Massaferro, Julieta; Brooks, Stephen J. (CHIRONOMUS Journal of Chironomidae Research)
Patagonia is the southernmost territory of South America and was traditionally considered as belonging to the Neotropical region (Sclater 1858, Wallace 1876). Based on these zoogeographic schemes, the Argentinean biogeographer Raul Ringuelet (1961) divided Patagonia into the Araucanian Subregion, characterized by dominance of Austral or Notogeic fauna, and the Andean-Patagonian Subregion, having a dominant mixture of Notogeic, Brasilic, and Nearctic elements. Later, Cabrera & Willink (1973) proposed a biogeographic scheme for South America and the Caribbean in which the Andean-Patagonian region was part of the Neotropical region and Araucania. They named the region the SubAntarctic province, which was part of the Antarctic region and was based on the floristic and faunistic affinities of southwestern Patagonia with Antarctica, Australia and New Zealand. Further biogeographic schemes considered Patagonia as a part of a Holantarctic region (Takhtajan 1986) or Sub-Antarctic subregion and Patagonian subregion of the Andean Region (Morrone 2001). The extraordinary amount of different biogeographic schemes reflects the complexity of the affinities of the biota of Patagonia. Fil: Donato, Mariano Humberto. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Sistemática y Biología Evolutiva; Argentina Fil: Massaferro, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Brooks, Stephen J. Natural History Museum; Reino Unido